Application of a sandwich hybridisation assay for rapid detection of the Northern Pacific seastar, Asterias amurensis - KF Smith; LL Rhodes; JE Adamson; JV Tyrrell; DO Mountfort; WJ Jones (New Zealand Journal of Marine and Freshwater Research, 2011)
A sandwich hybridisation assay (SHA) has been developed to detect Asterias amurensis (Lütken 1871), commonly known as the northern Pacific seastar, which is an unwanted, and as yet undetected, pest in New Zealand waters. Probes in SHA format have been developed that target the ribosomal RNA internal transcribed spacer region of A. amurensis. The successful assay utilises the capture probe ITS‐C2‐110 and the combined signal probes ITS‐S1‐93 and ITS‐S3‐240. It has been successfully tested for specificity, including cross‐reactivity testing against the common and related seastars, Patiriella regularis (Verrill 1867), P. mortenseni (O'Loughlin et al. 2002), Coscinasterias muricata (Verrill 1867) and Stichaster australis (Verrill 1871). The SHA is a rapid and potentially portable RNA‐based test, and opens up the opportunity for direct analysis of water samples, for example, portside during surveillance of marine pests.